2019
DOI: 10.18203/2394-6040.ijcmph20191832
|View full text |Cite
|
Sign up to set email alerts
|

A study on unhealthy cervix and its risk factors among currently married women of reproductive age group attending an urban health centre of Kolkata

Abstract: Background: Cancer of cervix is the third most common cancer in women in India accounting for 21.7% of cancer deaths among women. Unhealthy cervix, characterized by presence of any abnormal growth, ulcer, or vasculature, is a clinically detectable early stage in the life history of cervical cancer. Very few studies have been conducted to determine risk factors of unhealthy cervix.Methods: A clinic-based cross-sectional study was conducted among currently married women of reproductive age group attending Urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the study that included only cases of low and high squamous epithelial lesions reported Ki-67 expression in all the cases but reported higher scores (2+/3+) in only 32.3% of cases. 33 In another study Ki-67 expression in all the premalignant as well as malignant cases was moderate to high expression was seen in 70% of cases. In other studies, too, majority of CIN and carcinoma cases have been shown to have a positive Ki-67 expression.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the study that included only cases of low and high squamous epithelial lesions reported Ki-67 expression in all the cases but reported higher scores (2+/3+) in only 32.3% of cases. 33 In another study Ki-67 expression in all the premalignant as well as malignant cases was moderate to high expression was seen in 70% of cases. In other studies, too, majority of CIN and carcinoma cases have been shown to have a positive Ki-67 expression.…”
Section: Discussionmentioning
confidence: 89%
“…The natural history of cervical cancer represents a stepwise-progression from a histologically normal to frank invasive cancer. 5 Cervical cancer is considered to be a multifactorial disease involving socioeconomics, cultural, immunological and epigenetic factors, as well as persistent human papilloma virus (HPV) infection presence of factors like smoking, high parity, inflammation and other inducing factors like heavy viral load and presence of specific viral variants (HPV type 16,18,31,33,45, 58 and others) result in progression to higher grades and cervical intraepithelial neoplastic Department of Pathology, Hind Institute of Medical Sciences, Mau, Sitapur, Uttar Pradesh, India conditions which eventually progress to the invasive form of cervical cancer. Cervical cancer is a progressive disease which if identified at early stages of development could be prevented successfully from advancement and progression to more invasive stages.…”
Section: Introductionmentioning
confidence: 99%